Analysis of the Impact of Monetary Policy on Indonesia's Economic Stability in 2024 - Sutajri Sutajri; Muhammad Iqbal Fasa (DPPM Universitas Pelita Bangsa, 2024)
This research analyzes the impact of monetary policy on Indonesia's economic stability in 2024. Given the global uncertainty and domestic challenges experienced, monetary policy is a meaningful instrument in protecting inflation stability, exchange rates and economic development. The method used is regression analysis with time series information from Bank Indonesia and the Central Statistics Agency. The research results show that changes in interest rates and money market interventions have a significant impact on inflation and economic development. Not only that, monetary policy that is responsive to global economic conditions can mitigate the risk of uncertainty, which in turn contributes to macroeconomic stability. These findings are expected to provide suggestions for policy makers in designing more efficient monetary strategies to face future challenges.